Prediction of Mental Disorders Deprived by Family - Sri Mugianti; Suprajitno Suprajitno (Universitas Airlangga, 2014)
Introduction: The family was the place and the fi rst to meet the basic needs of human beings, has fi ve tasks in health. The inability of the family perform its tasks will be a problem in a family member suffering from a mental disorder, so allow the deprivation occurred. The aim of this study was to formulate the possibility of deprivation of people with mental disorders by family.Methods: The study design was cross sectional. Study subjects by 45 families who have family members with mental disorders from four clusters at health centres of Bacem Ponggok and Sutojayan of Kabupaten Blitar, selected by cluster random sampling with rapid survey. Analysis using nominal regression with α = 0.05.Results: Two tasks the family that affect was deprived of the ability of families caring for patients with signifi cant value 0.009 and the ability of families utilizing health care facilities with signifi cant value of 0.034. The possibility of patients to be deprived by family was formulated. Conclusion: Influences family task was 37.1% (Nagelkerke = 0.371) whereas 62.9% influenced by other factors. To minimize the occurrence of deprived be expected to treat patients with a family of faith, love, and use of health service facilities.